ANTIBACTERIAL AND ANTIFUNGAL ACTIVITY OF HERBAL MEDICINE CONTAINING ALUM AS MEDICINE PREPARATION FOR VAGINAL DISCHARGE - Ashfia, Finna; Taufikurohmah, Titik; Suyatno; Apriyosa, Eka (International Journal of Research -GRANTHAALAYAH, 2020)
Background: Vaginal discharge can caused by bacteria and fungi. Vaginal discharge treatment can be done through the use of herbal medicines that has lower side effects compared to synthetic drug. The 'X' alum herbal medicine used in this research containing majakani, betel leaf, henna leaf, gambier, turmeric, and alum. The research aims to determine the antibacterial and antifungal activities of alum herbal medicine against Neisseria gonorrhoeae and Candida albicans. Method: The methode used was disk diffusion. Results: Antibacterial testing was constrained by the presence of inhomogeneous samples and the separation of alum from the solvent used, so the data obtained was considered to be less valid. While the antifungal test has the largest inhibition zone of 11.98 mm at concentration of 50%. Expansion of the concentration is carried out to determine the inhibitory zone in the actual use of herbal medicine expressed in 100% concentration. The results of inhibition zone diameter of 100% was 15.6623 mm. This result show that at 100% this herbal medicine has almost the same activity as the synthetic drug which is quite effective in inhibiting the growth of fungi. Conclusions: This research provided that herbal medicine has antifungal activity that almost effective as Ketoconazole.